The Administration of a Combined Extract of Gotu Kola (Centella asiatica) and Peppermint (Mentha piperita) Leaves on the Brain Cell Count of Stressed Male Mice (Mus musculus) - Padmiswari, Anak Agung Istri Mas; Wulansari, Nadya Treesna; Harditya, Kadek Buja (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Chronic stress is a condition that can adversely affect the central nervous system, particularly the brain, by causing damage to neurons in the hippocampal region, which plays a crucial role in memory and learning functions. This study aimed to evaluate the neuroprotective effects of a combined extract of gotu kola leaves (Centella asiatica) and peppermint leaves (Mentha piperita) on the number of normal brain cells in male mice (Mus musculus) subjected to chronic stress. A Completely Randomized Design (CRD) was used with five treatment groups: a negative control group (K−) with no stress and no extract, a positive control group (K+) exposed to stress without extract administration, and three treatment groups (P1, P2, and P3) receiving the combined extract at doses of 100 mg/kg BW, 200 mg/kg BW, and 300 mg/kg BW, respectively. Stress induction was carried out using the immobilization method for 14 consecutive days, followed by extract administration for 35 days. After the treatment period, hippocampal brain tissue was collected and histologically analyzed using Hematoxylin-Eosin (H&E) staining. To assess the treatment effects, One-Way ANOVA was performed. Significant differences were found, Duncan’s Multiple Range Test (DMRT) was conducted at a 5% significance level (p< 0.05). The results demonstrated that administration of the gotu kola and peppermint extract combination significantly reduced neuronal damage and increased the number of normal brain cells. The P3 group (300 mg/kg BW) exhibited the highest number of normal brain cells and the lowest neuronal damage scores, closely resembling the normal condition in the K− group. Therefore, the combination of gotu kola and peppermint leaf extracts shows potential as a natural neuroprotective agent in mitigating the adverse effects of chronic stress on the brain.